PERSEPSI MAHKAMAH KONSTITUSI TENTANG HUTAN ADAT PASCA PUTUSAN NO. 35/PUU-X/2012 - Fitria Esfandiari (Legality : Jurnal Ilmiah Hukum, 2018)
Law No. 41 of 1999 concerning Forestry normatively provides recognition of the rights of indigenous peoples to forests. However, the issue of customary forest rights has led to various interpretations resulting in sectoral conflicts. This paper analyzes how the Constitutional Court's perceptions can postulate decisions regarding this customary forest issue. Decision of the Constitutional Court Number 35 / PUU-IX / 2012 in the case of Judicial Review of Law Number 41 of 1999 concerning Forestry against the 1945 Constitution of the Republic of Indonesia states that the position of the customary forest which currently exists within the territory of the customary law community the rights of indigenous and tribal peoples as long as in reality they still exist and are recognized. It also does not conflict with national interests in accordance with the development of society and the principles of the unitary state of the Republic of Indonesia as stipulated in the law. The research method used is a normative research method with a statutory approach. Literature study of related reading. The results showed that based on the Constitutional Court Decree Number 35 / PUU-IX / 2012 that, First, the recognition of customary forest is not state forest, Secondly, the customary forest that is intended is part of the customary area or called customary community's customary rights. Third, community rights will be recognized if the existence of indigenous peoples is determined through local regulations.